أدوات الحد من الفساد المالى وردعه فى المصارف: دراسة استطلاعية في عينة من المصارف العراقية - الشعباني، صالح إبراهيم يونس; حمد أمين، دشتي خالد Hamdamin, Dashti Khaled; خضر، جرجيس مصطفى (جامعة صلاح الدين, 2018)
تمثل هذه الدراسة محاولة لتسليط الضوء على مفهوم الفساد المالي ومسبباته وأنواعه في المصارف وماهية الطرق والوسائل للحد منه وردع من يتعامل به، والفساد هو كل قول أو فعل يتنافى ويتعارض مع الأخلاق والسلوك السوي حيث بدأت بوادر تشخيص تلك الظاهرة لدى الملك (حمورابي) في شريعته، وبعد أن كانت تلك الظاهرة مقتصرة على الواقع الداخلي فحسب أصبحت تمارس على نطاق عالمي وغدت هنالك جهات تستفيد من زيادة سلوكها المنحرف وتعدد سبلها الملتوية. وبالتالي فان التصرف غير المشروع يعد فسادا، وفي الجانب المالي يمثل الفساد استنزاف لراس المال العام أو استغلال القانون المالي أو التعليمات المالية أو تجاهلهما، وغالبا ما يرتبط الفساد المالي بالغش أو الاحتيال، حيث يشتركان سوية لتحقيق منافع شخصية تتعلق بتفضيل المصلحة الشخصية على المصلحة العامة، كما تعد حالات غسيل الأموال وتهريبها ضربا خطيرا من الفساد المالي لاسيما في ظل بيئة مصرفية متعاونة توفر المناخ الملائم لممارسة أوجه ذلك الفساد. وبالتالي لابد من اعتماد أدوات وأساليب فعالة وكفؤة من اجل اكتشاف مواطن الخلل والتلاعب المالي والحد منه وردع من يتعامل به. وتعد المحاسبة القضائية ونظام الرقابة الداخلية وقوانين أو تعليمات الحوكمة من بين أهم تلك الأدوات. وعليه وفد بنيت الدراسة على فرضية مفادها " أن تبني أدوات فعالة وأساليب رشيدة في ممارسة الأنشطة الوظيفية واعتماد القوانين والضوابط والمعايير السليمة في المصارف يقضي على ظاهرة الفساد المالي ويردع مرتكبيه ". واعتمد المنهج الاستقرائي في صياغة البحث ثم الاستنباطي التحليلي، حيث تم استخدام استمارة الاستبانة لغرض جمع المعلومات وتم توزيع (80) استمارة أما عدد الاستمارات المرتجعة والصالحة قد بلغت (70) استمارة، وقد توصل البحث إلى مجموعة من الاستنتاجات من أهمها أن هناك عدة طرق وأساليب يمكن أن تساهم في مكافحة الفساد المالي ومنها نظام الرقابة الداخلية والبعد الأخلاقي وكذلك استخدام المحاسبة القضائية وتطبيق قواعد الحوكمة، وعليه أوصى الباحثون على الشركات عامة والمصارف خاصة تطبيق قواعد الحوكمة لما لها من دور فعال في محاربة الفساد المالي بكل أشكاله.
This study is an attempt to shed light on the concept of financial corruption and its causes, and it's types in banks, and what are the ways and means to reduce it and deter those who deal with it. Corruption is any saying or action that contradicts morality and normal behavior, where signs began to diagnose this phenomenon with the king (Hammurabi) in his law, and after the phenomenon was limited to the internal reality, but has been practiced on a global scale and there are those who benefit from increased behavior deviant and plural Her twisted ways. Corruption is a drain on public capital or the exploitation or neglect of financial law or regulations. Financial corruption is often associated with fraud, where they share common personal interests in favor of the public interest, Money laundering and smuggling are a serious blow to financial corruption, especially in a cooperative banking environment that provides a suitable environment for practicing such corruption. Therefore, it is necessary to adopt effective tools and efficient methods in order to detect and reduce the imbalances and financial manipulation and deter those who deal with it. forensic accounting, internal control, and governance laws or regulations are among the most important. The study was based on the hypothesis that say " the adoption of effective tools and rational methods in the practice of functional activities and the adoption of laws, On the phenomenon of financial corruption and deter the perpetrators". Then Use the descriptive approach in the formulation of research and analytical approach The questionnaire was used for the purpose of collecting information and 80 forms were distributed. The number of returned and valid forms reached (70) form. The research reached a number of conclusions, the most important of which are that there are several methods and methods that can contribute to combating financial corruption, Internal and moral dimensions, as well as the use of judicial accounting and the application of the rules of governance. Accordingly, the researchers recommended companies in general and banks in particular to apply the rules of governance because they have an effective role in combating financial corruption in all its forms.
Keywords: الحوكمة الرشيدة -- الرقابة المالية -- المصارف العراقية -- حقوق الإنسان